Wage versus currency devaluation, price pass-through and income distribution: A comparative input-output analysis of the Greek and Italian economies - Theodore Mariolis; Nikolaos Rodousakis; Apostolis Katsinos (Journal of Economic Structures, 2019)
Using input-output data from Symmetric Input-Output Tables for the year 2010 and relevant price models, this paper provides empirical estimations of medium- and long-run effects of wage and currency devaluations on international price competitiveness and income distribution for two 'PIIGS economies', i.e. Greece and Italy. The findings reveal certain differentiated socio-technical production conditions in the economies under consideration casting doubt on the effectiveness of demand-switching policy measures implemented in the post-2010 Eurozone economy. At the same time, however, wage devaluation is found to be a comparatively slow and inefficient process to improve international price competitiveness in the medium-run.
Keywords: C67; D57; E11; E64; 330; Income distribution; Input-output price models; International price competitiveness; PIIGS economies; Price pass-through; Wage and currency devaluations